Use of FTA® classic cards for epigenetic analysis of sperm DNA. (February 2018) - Serra, Olga; Frazzi, Raffaele; Perotti, Alessio; Barusi, Lorenzo; Buschini, Annamaria
FTA ® technologies provide the most reliable method for DNA extraction. Although FTA technologies have been widely used for genetic analysis, there is no literature on their use for epigenetic analysis yet. We present for the first time, a simple method for quantitative methylation assessment based on sperm cells stored on Whatman FTA classic cards. Specifically, elution of seminal DNA from FTA classic cards was successfully tested with an elution buffer and an incubation step in a thermocycler. The eluted DNA was bisulfite converted, amplified by PCR, and a region of interest was pyrosequenced.